Adult attachment style and therapeutic alliance in men who assault their partners - Lazo Bazán, Wilson Omar (2016)
In order to develop strategies to facilitate the establishment of a positive therapeutic alliance, which is considered the main predictor of therapeutic success in the intervention with men who use violence against their partners (partner violence perpetrators), this study aims to analyze whether there is a significant relationship between adult attachment styles and the establishment of a positive therapeutic alliance in the psychotherapeutic intervention with partner violence perpetrators. The results confirm the existence of this relationship; also, it is found that the Hostile Fearful attachment style presents problems to establish a positive therapeutic alliance. Given these findings the authors discuss the importance that therapists consider the adult attachment style of these men in order to foster therapeutic alliance; also, additional implications are analyzed for future research to improve clinical practice.